The Role of Exercise in Regulating the Generation of Extracellular Vesicles in Cardiovascular Diseases - Peng Shen; Yue Qiu; Yan-Yan Sun; Yue-Ying Jiang; Xiu-Mei Guan; Min Cheng; Yan-Xia Wang (Reviews in Cardiovascular Medicine)
Extracellular vesicles (EVs) are nanoscale vesicles released by cells, which play an important role in intercellular communication by transporting proteins, lipids, nucleic acids, and other molecules. Different intensities of exercise can induce the release of EVs from cells and tissues, such as endothelial cells, skeletal muscle and adipose tissue, hepatocytes, immune cells, and neuronal cells. Exercise-induced EVs exert cardiovascular protective effects such as anti-inflammatory and anti-oxidative by altering their contents. This paper reviews the cell and tissue sources of EVs induced by exercise of different intensities, the regulatory effects of different exercise intensities on EVs, and their mechanisms of action in cardiovascular diseases. The aim is to provide new insights for the treatment of cardiovascular diseases and offer scientific evidence for the construction of engineered EVs mimicking the effects of exercise.